The impact of the financial revolution in England in 1688 on the development of financial services - S.Z. Moshenskyi (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The differences between the decentralized model of the British financial market from the centralized French (continental) model emerged after the financial revolution of 1688 in England, which lasted until the end of the XVII century and had an impact on public and private finance. Due to the captivity of the French Huguenots shortly before the "Glorious Revolution" in England, new technologies appeared in the financial sector, and manifested in the creation of the first British banks. After the revolution, with the coming to power of the Dutch Prince, many financiers arrived at London and were spreading the technique of effective Dutch stock transactions. Increased interest of the society to innovation in the financial market and the emergence of new investment opportunities had a positive impact on the development of stock market, government bond market and derivatives market. This, in its turn, led to the appearance of new financial intermediaries such as jobbers, who took over the high risks because of investing of own funds in securities. Such significant changes in the financial system of England became the important prerequisite of the industrial revolution and allowed it to take the leading position in the economic, political and financial area in the world.